Change in awareness levels of cervical cancer among rural women after intervention by health education: a community-based study - Kalpana, G.; Gangadharan, Keshav; S., Pradeep; M., Devivaraprasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Cervical cancer is the fourth most common cancer among women worldwide. The prevention and control of cervical cancer depends on awareness about the disease, screening procedures, and preventive measures. Objectives of this study was to assess the awareness levels on various aspects of cervical cancer among women aged 25-65 years, and to assess the impact of health education intervention among them. Methods: This community-based interventional study was conducted for a period of 15 months among 250 women aged 25-65 years by cluster sampling method in a rural population. Data on all aspects of awareness about cervical cancer, i.e., risk factors, signs and symptoms, diagnosis and treatment and prevention were collected using a pre-tested semi-structured proforma. This was followed by a post-test 2 months after health education. Results: Overall awareness for cervical cancer was found to be very poor among the study subjects in the pre-test. Awareness on risk factors, signs and symptoms, diagnosis and treatment, and prevention of cervical cancer was found to be 6%, 3.6%, 1.2%, and 1.6% respectively. A significant increase in the knowledge level was found after health education. Conclusions: As the awareness levels regarding the cervical cancer was poor among the study population, health education programme and campaigns, along with periodic screening is need of the hour to effectively prevent cervical cancer.